PENGARUH TIPE SALURAN PENGECORAN TERHADAP SIFAT MEKANIK DAN STRUKTUR MIKRO ALUMINIUM AL 6061 DENGAN METODE SAND CASTING - Heni Hendaryati; Mohamad Irkham Mamungkas (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2021)
Industrial technology is developing very rapidly, one of which is in the field of metal casting. In the foundry case, aluminum is one of the most used types. It happen because of aluminum has many advantages than other types of metal, likely: good corrosion resistance, relatively high mechanical properties, and good formability. The purpose of this study was to determine the effect of variations in the duct system on the tensile strength and impact strength of Al 6061 aluminum using the sand casting method. A variation of this line system was to use a direct line, split line, and split line with an adder. From the results of the study, it was found that the ultimate tensile strength occurred in the specimens using a split channel pattern with an adder, which was 120.25 MPa, while the lowest tensile strength occurred in the specimens using a direct channel pattern which was 65,49 MPa. This also occurs for the highest impact value in the variation of the split pattern system with addition of 0.0081 J/mm2 and the lowest impact value is using the direct channel pattern which results in an impact value of 0.005508 J/mm2